Multi‐criteria decision analysis for flood risk on the Chenab River. (24th April 2019) - Hassan, Sher Shah; Ajmal, Muhammad; Khan, Aftab Ahmad; Goheer, Muhammad Arif; Khattak, Muhammad Shahzad; Ali, Shaukat; Ijaz, Muhammad; Adnan, Muhammad
Abstract :